Review on dissimilar structures joints failure. (November 2021) - Correia, Arménio N.; Braga, Daniel F.O.; Moreira, Pedro M.G.P.; Infante, Virgínia
Highlights: Review on the failure modes associated to dissimilar FSW joints. Comprehensive analysis and enumeration of the different cases available in the literature. Static strength and defects, fatigue behavior and crack growth, and corrosion proneness and corrosion cracking. Abstract: Fuel economy has become, more than ever, one of the central keys around which the industrial development of transportation means (mainly aeronautics and aerospace) orbits around. In order to improve fuel consumption efficiency, lightweight and multipurpose dissimilar structures are pushing the boundaries of innovation through generative design, joining of dissimilar materials through innovative technologies and advanced manufacturing systems, such as addictive manufacturing. Friction Stir Welding (FSW) and Laser Beam Welding and their hybrid technologies represent some of the solid-state welding technologies that play significant roles in what concerns to join dissimilar materials such as Steels, Aluminum and Titanium alloys as well as high performance thermoplastics like Polyether Ether Ketone (PEEK) and Polyphenylene Sulphide (PPS). This article makes a review on the failure modes associated to dissimilar FSW joints, through a comprehensive analysis and enumeration of the different cases that are mentioned in the literature. Initially, it will be reviewed the state of the art related to the technological processes and materials categorization, as well as a summary of several papers and the respective reported failure modes, organized by static strength and defects, fatigue behavior and crack growth, and corrosion proneness and corrosion cracking.